Efficacy Test of Prototype Kit for Detection Bacillus cereus and Listeria monocytogenes in Processed Meat using Real-time PCR Method - Nurjayadi, Muktiningsih; Fahriza, Tiara; Putri, Adinda Myra Amalia; Rahmawati, Atikah Nur; Berkahingrum, Ayu; Anggraeni, Rosita Gio; Putri, Gladys Indira; Declan, Jefferson Lynford; Akbar, Dandy; Maulana, Irvan; Azzahra, Maharanianska; Shangkara, Muhammad Arkent; Kartika, Irma Ratna; Kurniadewi, Fera; Sukmawati, Dalia; Rahayu, Sri; Saamia, Vira; Wiranatha, I Made; Abumoelak, Bassam; El Enshasy, Hesham (Jurnal Kimia Valensi, 2025)
According to the World Health Organization (WHO), harmful agents such as Bacillus cereus and Listeria monocytogenes are responsible for 600 million cases of disease and 420,000 deaths annually. This research aims to test the effectiveness of the real-time PCR method for developing a prototype kit to detect pathogenic bacteria in processed meat. As a comparison, the and conventional PCR methods were used to obtain the accuracy, specificity, sensitivity, and effectiveness of the real-time PCR method. All the samples were cultured in solid media agar, performed amplification using specific primers cyt-K 2 and hly using PCR and real-time PCR. Meatballs, nuggets, and sausages, five samples each, were found to be positive positively contaminated with all targeted bacteria. However, they did not provide specific results using solid media culture and the PCR method. In addition, the real-time PCR method using prototype kit formulas accomplished that all contaminated samples had a Ct value smaller than the negative control, NTC (No Template Control), and had a similar melting curve to the positive control. This establishes that the real-time PCR method clarifies that all samples were contaminated with target bacteria. A formula was developed in the prototype kit with real-time PCR methods that can be used and applied on a commercial scale efficiently and precisely.